Review of formulas to describe the fatigue crack growth rate - Rozumek, D. (Фізико-хімічна механіка матеріалів, 2013)
The paper presents a review of formulas of fatigue crack growth rate. The equations are divided into three groups according to the fatigue damage parameters used, i.e. stress, strain or displacement and energy. The parameter K or its ∆K range corresponds to brittle materials and to the initial stage of the crack of elastic-plastic materials. The parameter ε or CTOD is used in elastic-plastic materials and plastic materials to describe the yield strength. The energy approach is based on J parameter or the strain energy density W and corresponds to the whole range of the crack growth rate curve.